2010
DOI: 10.5423/ppj.2010.26.4.340
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microbial Fungicides in Antagonistic Activities Related to the Biological Control of Phytophthora Blight in Chili Pepper Caused by Phytophthora capsici

Abstract: Two similar microbial fungicides (termed as MA and MB) developed in a Korean biopesticide company were analyzed and compared each other in their biocontrol activities against the phytophthora blight of chili pepper caused by Phytophthora capsici. MA and MB contained the microbe Paenibacillus polymyxa and Bacillus subtilis, respectively, with concentrations over those posted on the microbial products. In comparison of the isolated microbes (termed as MAP from MA and MBB from MB) in the antagonistic activities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Of the endophytes evaluated in this study, A22F1 (Nigrospora sphaerica) has been reported to be a plant endophyte in medicinal plants, sea grass, palm trees, tomato, and pepper [48]. Various studies have identified novel metabolites from N. sphaerica, some of which have antifungal properties [51]. Although the production of many of these metabolites by the endophytic fungi are not fully understood or known, a compound, phomalactone (5, 6-dihydro-5-hydroxy-6-prop-2-enyl-2H-pyran-2-one) produced by N. sphaerica has been reported to inhibit mycelial growth of Phytophthora infestans and sporangia and zoospore germination of both P. infestans and P. capsici [12].…”
Section: Discussionmentioning
confidence: 99%
“…Of the endophytes evaluated in this study, A22F1 (Nigrospora sphaerica) has been reported to be a plant endophyte in medicinal plants, sea grass, palm trees, tomato, and pepper [48]. Various studies have identified novel metabolites from N. sphaerica, some of which have antifungal properties [51]. Although the production of many of these metabolites by the endophytic fungi are not fully understood or known, a compound, phomalactone (5, 6-dihydro-5-hydroxy-6-prop-2-enyl-2H-pyran-2-one) produced by N. sphaerica has been reported to inhibit mycelial growth of Phytophthora infestans and sporangia and zoospore germination of both P. infestans and P. capsici [12].…”
Section: Discussionmentioning
confidence: 99%
“…as biocontrol agents against soil-borne plant pathogens is advantageous because they form endospores, easily colonize plant roots, produce broad-spectrum antibiotics, and promote plant growth [43]. The ability of Bacillus spp to form endospores make them more resistant to harsh environmental conditions, more tolerant to chemical fungicides and easier to formulate into commercial biofungicides with longer viability and shelf-life in comparison to other BCAs that are non-endospore formers [14]. Some Bacillus-based biopesticides such Kodiak, Companion, Serenade, and Rhapsody are currently being sold and used against many important plant pathogens [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Disease development is favored by warm temperatures, high rainfall or irrigation, and poor soil drainage [8]. The disease is managed mainly by crop rotation, application of chemical fungicides such as metalaxyl or mefenoxam, and management of irrigation water [12][13][14][15]. However, it is difficult to manage Phytophthora diseases because of the long-term survival of oospores in the soil, wide host range, and long-distance movement of the pathogens through soil and water [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our study, a previous study documented a much higher number (27.5-62.6%) of bacterial antagonists to the common plant pathogenic fungi Rhizoctonia solani, Py. ultimum, Fusarium oxysporum, and Botrytis cinerea in eight coastal dune plants (Kim et al, 2010;Shin et al, 2007). This may be because we used only oomycetes as target organisms, while in the previous study the initial screening included many target pathogens.…”
Section: Discussionmentioning
confidence: 99%